Genome-Wide Association Study of Glucosinolate Metabolites (mGWAS) in Brassica napus L. - Yunshan Tang; Guorui Zhang; Xinyue Jiang; Shulin Shen; Mingwei Guan; Yuhan Tang; Fujun Sun; Ran Hu; Si Chen; Huiyan Zhao; Jiana Li; Kun Lu; et al. (Plants, 2023)
Glucosinolates (GSLs) are secondary plant metabolites that are enriched in rapeseed and related Brassica species, and they play important roles in defense due to their anti-nutritive and toxic properties. Here, we conducted a genome-wide association study of six glucosinolate metabolites (mGWAS) in rapeseed, including three aliphatic glucosinolates (m145 gluconapin, m150 glucobrassicanapin and m151 progoitrin), one aromatic glucosinolate (m157 gluconasturtiin) and two indole glucosinolates (m165 indolylmethyl glucosinolate and m172 4-hydroxyglucobrassicin), respectively. We identified 113 candidate intervals significantly associated with these six glucosinolate metabolites. In the genomic regions linked to the mGWAS peaks, 187 candidate genes involved in glucosinolate biosynthesis (e.g., BnaMAM1, BnaGGP1, BnaSUR1 and BnaMYB51) and novel genes (e.g., BnaMYB44, BnaERF025, BnaE2FC, BnaNAC102 and BnaDREB1D) were predicted based on the mGWAS, combined with analysis of differentially expressed genes. Our results provide insight into the genetic basis of glucosinolate biosynthesis in rapeseed and should facilitate marker-based breeding for improved seed quality in Brassica species.